Referee height influences decision making in British football leagues - McCarrick, Dane (BMC Psychol, 2020)
BACKGROUND: Male height is positively associated with social dominance, and more agonistic/competitive behaviours. However, the ‘Napoleon complex’ or ‘small man syndrome’ suggests that smaller males are more assertive and punitive to compensate for lack of height and social dominance. Here, we assess possible relationships between height and punitive behaviours in a real-world setting. METHODS: Using a non-experimental correlational design, we analysed data on 61 male association football referees from four professional leagues in England, and explored relationships between their height and punitive behaviours in the form of yellow cards, red cards and penalties given during an entire season. RESULTS: Overall there was no effect of referee height on fouls awarded. However, there was a main effect of height on yellow cards awarded, with shorter referees issuing more yellow cards. The same effect was found for red cards and penalties, though this was moderated by league. In the lower leagues, more red cards and penalties were awarded by relatively shorter referees, but in the higher leagues more red cards and penalties were awarded by relatively taller referees. CONCLUSIONS: These findings from real-life public dominance encounters show that height is associated with punitive behaviours, but is sensitive to context.